Systematic Literature Review: Analisis Pemecahan Masalah Matematika Mahasiswa dan Siswa dengan Berpikir Komputasional - Syifa Husna Ramadhani; Yahfizham Yahfizham (LPPM Politeknik Pratama, 2024)
Usually thinking is often associated with mathematics. In the 21st century, technological developments are increasingly rapid so that computational thinking is very important for students and students. Computational thinking is thinking that involves understanding problems, reasoning, and also developing solutions automatically. Based on these computational thinking skills, it will help students and students solve problems mathematics by simplifying complex problems into simpler aspects and can also make it easier for students and students to understand and solve problems in mathematics problems that have been given previously. The aim of the research was to analyze the mathematical problem solving abilities of both students and students with computational thinking using the Literature Review Study method which focuses on solving students' and students' mathematical problems with computational thinking.